Monarch and Court in Mediaeval Serbia - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The Serbian Mediaeval State was a monarchy where the ruler exercised supreme powers with legislative, military, diplomatic and judicial competences. The kings also claimed property right over the whole territory of the State (dominium eminens). However, diverse types of institutional representation completed the governmental structure. State Councils exercised a great influence. They were representative body comprising the most powerful lords, secular and ecclesiastical. The sources also mention the existence of various court dignitaries and local civil servants. The most important cout dignitaries comprised the kaznac (tax collector) and the tepčija (land official). In the administrative reform of 1340, under King Dušan, new titles and offices were introduced, mostly as a result of the Byzantine influence. These new titles included the logothet (chancellor), the protovestijar (chamberlain,) the great čelnik (comes palatinus) and  dvorodržica (marshal of the court), while on the local level, a new office of kefalija (capitaneus) was created. A few Serbian and Byzantine narrative sources point also to the existence of a Privy Council that regrouped the highest nobility of the kingdom.